(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Festivals such as "Boysun Bahori" have a great role in the preservation of folklore songs in folk art for thousands of years. Especially young talents are discovered by participating in the festival. serves to increase the interest of our young people in our ancient art. After all, our national festivals such as Boysun Spring are eternal.